Improving Heat Efficiency of Aniline Production Process by Modifying Heat Transfer Fluid Looping System in Heating and Cooling Process - Ahdan, Muhammad; Saputra, Alfan Rizky; Ivan, Rifqy; Panjaitan, Yohanes Mangarohontua (UPT Laboratorium Terpadu, Universitas Diponegoro, 2024)
The nitrobenzene hydrogenation process is a highly exothermic reaction which causes the product temperature will increase and then needs to be cooled down with a heat exchanger. The modification process is needed to improve the heat efficiency of the nitrobenzene hydrogenation process by utilizing the heat from reactor product. Heat transfer fluid is used as a medium of heat transfer for both heating and cooling, so that will create a looping heat transfer process. The looping system of heat transfer fluid receives heat from reactor product and then reuses the heat to reheat the recycled hydrogen and for other utilities, so additional energy for these processes is not required. The process modification was simulated using Aspen HYSYS and the comparison of heat efficiency between the basic and the modified process is calculated using the net-energy formula. The results obtained that the net-energy (NE) value for both basic and modified process is 96,714,359.832 kJ/h and 9.869 kJ/h. This shows that the modified process has better energy efficiency compared to the basic process as the net-energy value is closer to zero. Therefore, this modification increases the heat efficiency of the aniline production through nitrobenzene hydrogenation process. Copyright © 2024 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).